PEMBERDAYAAN DAN PERAN KELOMPOK TANI DALAM USAHATANI PADI SAWAH DI KABUPATEN BONE - Eva Afriana Gani; Nuraeni Nuraeni; Aminah Aminah (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
The research was conducted to 1)Analyze the empowerment of farmer groups in the management of lowland rice farming in Toro Village, 2 Analyze the role of farmer groups in the management of lowland rice farming in Toro Village, 3)Analyze the production and income of lowland rice farming in Toro Village, 4)Analyze the influence of empowerment of farmer groups on the productivity of lowland rice in Toro Village, and 5)Analyzing the influence of the role of farmer groups on the productivity of lowland rice farming in Toro Village. The research was conducted in Toro Village, Tanete Riattang Timur District, Bone Regency in October-November 2021 from 17 farmer groups. Survey research method with purposive sampling, with 51 farmers as a sample. Farmer groups in Toro Village through the ability of farmer groups in managing information, managing farms, market production and application of technology are included in the very good category with an index of 82.9%. The role of farmer groups in Toro Village as a place of learning, a vehicle for cooperation and production units play a good role in increasing the productivity of lowland rice farming. Lowland rice farming is profitable for farmers with an average income of lowland rice in Toro Village of Rp. 22,084,070 and the average total cost of production is Rp. 3,260,108 and the average income of farmers per planting season is Rp. 18,823,963. Empowerment of farmer groups in Toro Village through the ability of farmer groups in managing information, decision making, farm management, production marketing and application of technology has a significant effect on increasing rice farming productivity in Bone Regency. The role of farmer groups as a learning platform, a vehicle for cooperation and production units has no significant effect on increasing the productivity of lowland rice farming in Bone Regency.